Performance mapping of a two-stage travelling wave thermoacoustic engine for heat recovery - Goh, Jenn Hsen (2019)
This thesis describes the characterization of the performance of a Two-Stage Travelling Wave Thermoacoustic Engine, called the DEMO 2 Engine. Preliminary experiments on the DEMO 2 Engine showed that its performance level was far below its design expectations. Thus, an analytical approach was developed to investigate the sources of losses that were affecting the performance of the DEMO 2 Engine. The approach involves studying the heat transfer and acoustic performance of the DEMO 2 Engine as well as constructing a numerical model of the DEMO 2 Engine.